Impact Of Financial Technology’s Growth to Bank’s Performance and Efficiency at Pre Pandemic Covid-19 - Chairunnisa, Bella Ananda (MBIA, 2023)
COVID-19 outbreaks are known as catalysts of digitalization in all industries, including the financial industry, because of the emergence of financial technology. Prior research often illustrated the impact of emerging financial technology on industries at the moment or during a pandemic. However, little attention has been devoted to these impacts during the pandemic. Given a sight from the consumer's perspective, we tried to examine the causality between financial technology's growth and the bank's performance and efficiency. We utilized conventional banks as our population with sample criteria listed banks in Southeast Asia from 2017 to 2019. We employed generalized least squares and the generalized method of moment as regression methods to examine those causalities. Descriptive statistical analysis, determining estimation models, and classical assumption tests were also carried out. A total sample of 102 banks, Our findings suggest that ever since pre-pandemic, financial technology has significantly impacted banks' performance and efficiency. The growth of financial technology caused a significant decrease in the bank's performance and an increase in the bank's efficiency. Keywords: Financial Technology, Performance, Efficiency, Banking, Pre-Pandemic Abstrak Wabah Covid-19 diketahui menjadi katalis digitalisasi pada semua industri termasuk industri keuangan melalui munculnya teknologi keuangan. Penelitian sebelumnya sering menjelaskan mengenai dampak teknologi keuangan pada saat atau pasca pandemi. Namun, masih sedikit penelitian yang berfokus pada dampak tersebut sebelum pandemi terjadi. Melihat dari sudut pandang konsumen, peneliti mengkaji hubungan sebab akibat antara pertumbuhan teknologi keuangan terhadap kinerja dan efisiensi bank. Menggunakan populasi bank konvensional dengan kriteria sampel bank yang terdaftar di bursa Asia Tenggara pada tahun 2017 hingga 2019. Peneliti mengoperasikan Generalized Least Square dan Generalized Method of Moment sebagai metode regresi untuk menguji hubungan tersebut. Selain itu dilakukan juga analisa descriptive statistic, determining estimation model, dan uji asumsi klasik. Dengan total sampel 102 bank, temuan menunjukkan bahwa sejak sebelum pandemi, teknologi keuangan telah berdampak signifikan terhadap kinerja dan efisiensi bank. Pertumbuhan teknologi finansial menyebabkan penurunan kinerja bank secara signifikan dan peningkatan efisiensi bank Kata kunci: Teknologi Finansial, Kinerja, Effisiensi, Perbankan, Pra Pandemi